Efficacy of localized intradermal microinjection of tranexamic acid at a concentration of 4 mg/ml in the treatment of melasma in Syria - Al-Manssour, Heba Ghassan; Roumieh, Abdulhalim (Journal of medical and pharmaceutical sciences, 2022)
Background: Melasma is a common acquired hyperpigmented dermatosis due to a disorder in the function of the melanogenesis process. Nowadays, there are many used treatments for melasma but it is still a big cosmetic problem.The Aim of our study is to evaluate the efficacy and safety of intradermal microinjection of tranexamic acid TXA in the treatment of melasma in Syrian women.Methods: A total of 34 women with melasma, attending Tishreen University Hospital in Lattakia-Syria from January 2020 to January 2021 were included in this prospective (before and after) study. We applied topical anesthesia then we injected 0.05 ml TXA (4 mg/ml) intradermally into the melasma lesions at 1 cm intervals by using a 30-gauge insulin syringe. We repeated this procedure every 2 weeks for 12 weeks. A clinical investigator evaluated the results by using the modified Melasma Area and Severity Index (mMASI) at baseline and at 4, 8, and 12 weeks. Patients were followed up after 3 months from completing the treatment.Results: The mean mMASI scores decreased from 6.99±3.4 at baseline to 5.98±3.2, 4.59±2.5 and 3.49±2.3 at weeks 4, 8, 12 respectively. This decrease was clinically and statistically significant with a p-value = 0.0001.Our patients did not show serious side effects.Conclusion: According to that, we suggest that localized intradermal microinjection of tranexamic acid at a concentration of 4 mg/ml is an effective and safe therapeutic method for melasma.
Keywords: Melasma; mMASI; tranexamic acid TXA